2019
DOI: 10.1039/c9ra06414a
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free, room temperature, acid-K2S2O8 mediated method for the nitration of olefins: an easy approach for the synthesis of nitroolefins

Abstract: Here, we have developed a simple, room temperature method for the nitration of olefins by using inexpensive sodium nitrite as a source of nitro groups in the presence of TFA and potassium persulphate under an open atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Nitroolefins were prepared according to the literature reported procedure and identified by comparison of melting point/ 1 H NMR with the literature melting point/ 1 H NMR: 3a – c , 3d , 3e , 3f – i , 3j , 3l , 3m , and 3n – q and completely characterized with the detailed spectroscopic studies.…”
Section: Methodsmentioning
confidence: 99%
“…Nitroolefins were prepared according to the literature reported procedure and identified by comparison of melting point/ 1 H NMR with the literature melting point/ 1 H NMR: 3a – c , 3d , 3e , 3f – i , 3j , 3l , 3m , and 3n – q and completely characterized with the detailed spectroscopic studies.…”
Section: Methodsmentioning
confidence: 99%
“…Singh et al . published another simple stereoselective formation of nitrostyrenes using sodium nitrite and K 2 S 2 O 8 in the presence of trifluoroacetic acid as well 8 . All of these reactions granted an easy preparation of β‐nitrostyrenes, but it is necessary to execute the reactions at high temperature or use stoichiometric amounts of oxidants or strong acid.…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, several research groups overcome such problems by using appropriate combination of nitrogen sources and mild oxidants under transition-metal free conditions (Scheme 1). [6][7][8] Maiti et al developed the practical stereoselective nitration of styrenes with tert-butyl nitrite (TBN) and 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO). 6 Guo group also reported the nitration reactions of olefins with sodium nitrite, K 2 S 2 O 8 using TEMPO.…”
mentioning
confidence: 99%
“…In the last decades several research groups devised new methods for the direct nitration of olefins which are shown in scheme 21. [51][52][53][54] Katayev and co-workers in 2019 designed and developed a practical and bench-stable succinimide derived NO 2 -transfer reagent can liberate nitryl radical under mild and neutral conditions, thus allowing for the direct nitration of C(sp 2 )À H bonds of alkenes (Scheme 22). [55] This protocol also allows to access valuable nitrohydrin building blocks and functionalised isoxazole-motifs in an unprecedented and selective fashion using a single reagent in one-step.…”
Section: Notable Recent Reports On Nitration Of Olefinsmentioning
confidence: 99%
“…While our original reports were published in the year 2013, several notable development in the related field appeared in the literature in the subsequent years. In the last decades several research groups devised new methods for the direct nitration of olefins which are shown in scheme 21 [51–54] …”
Section: Direct Nitration Of Olefinsmentioning
confidence: 99%